The illegal trade of the Sumatran serow Capricornis sumatraensis sumatraensis for traditional medicine in Indonesia - Chris R Shepherd; Lalita Gomez; Biofagri A Rachmayuningtyas (Universitas Pakuan, 2022)
Mainland serow are in decline in Southeast Asia with poaching for illegal trade being a major driver. In Indonesia, where this species is found only on the island of Sumatra, the illegal wildlife trade is widespread and impacts numerous species and it is therefore not surprising to find serow in trade. Using seizure and prosecution data from 2014 to 2021, a total of 13 seizure records were obtained, involving an estimated minimum of 32 mainland serow (Capricornis sumatraensis). While legislation is in place in Indonesia to protect serow from poaching and illegal trade, meaningful penalties are seldom handed down. In an absence of effective deterrents, illegal trade will continue to be a threat to the conservation of this species.Kambing hutan daratan utama mengalami penurunan di Asia Tenggara yang mana perburuan untuk perdagangan ilegal menjadi pendorong utama. Di Indonesia, di mana spesies ini hanya ditemukan di Pulau Sumatra, perdagangan satwa liar secara ilegal terjadi dimana-mana dan berdampak pada banyak spesies, oleh karena itu tidak mengherankan jika ditemukan kambing hutan dalam perdagangan ilegal tersebut. Dengan menggunakan data penyitaan dan penuntutan mulai tahun 2014 hingga 2021, diperoleh total 13 catatan penyitaan, dengan perkiraan minimal terdapat 32 ekor kambing hutan (Capricornis sumatraensis). Meski undang-undang telah ada di Indonesia untuk melindungi kambing hutan dari perburuan dan perdagangan ilegal, namun hukuman yang dijatuhkan jarang sepadan. Tanpa adanya pencegahan yang efektif, perdagangan ilegal akan terus menjadi ancaman bagi upaya pelestarian spesies ini.